The Agricultural Changes of the Fifteenth Century - Davenport, Frances Gardiner; A., W. J. (Quarterly Journal of Economics, 1897)
Frances Gardiner Davenport; The Agricultural Changes of the Fifteenth Century, The Quarterly Journal of Economics, Volume 11, Issue 2, 1 January 1897, Page